Das finnische Mökkiwesen: Ein landestypischer Lebensstil im Umbruch? - Jäderholm-Vogel, Kristina; Steingrube, Wilhelm (ERDKUNDE, 1996)
To have a free-time residence of one’s own has been a long tradition in Finland. At the beginning (in the early 19th century) there were impressive summer villas belonging to a small and wealthy group of the population. After a period of slow but steady growth the demand for private leisure homes in Finland has risen exponentially since the Second World War. Nowadays it is no longer a privilege of a certain social or income class to own such a home. Meanwhile nearly every third family has its own Mökki, as the Finns call their summer cabin. The period of use is getting longer and longer, and the simple summer cabin has often become a free-time residence fit to live in all year round. Fundamental changes in political, economic and social conditions (economic crises, new planning regulations, ecological problems and so on) will, however, bring to a sudden halt a further increase in the number of free-time residences, possibly within a few years. Nevertheless, initial findings show dearly that many Finns are striving for their own Mökki or are maintaining emotional bonds with their family leisure home, which is of central importance to their lives, i. e. the Mökki has become an important component of their life-style. As this life-style component is spread across all social classes all over Finland we can speak of a national life-style. Most Finns do not consider their leisure houses as normal economic goods - they have strong emotional bonds with them. The Finnish Mökkis will therefore probably prove to be relatively resistant to negative external influences. For prognosticating the further development of the Mökki network it is therefore not sufficient to analyze the economic and objective general conditions. In order to draw up realistic scenarios we will have to pay special attention to the life-style conception or similar approaches which take the individual level of evaluation and decision into consideration.